Analisis Determinasi Kapasitas Fiskal Daerah Kabupaten/Kota di Sumatera 2019 - Doni Ardiansyah; Dedy Yuliawan (Journal on Education, 2024)
One of the successes of a country is the creation of good quality development in each region. Regional autonomy is a good opportunity for local governments to prove the ability of local governments to carry out the authority that is the right of the region. The potential financial capacity of a region cannot be separated from the factors of regional prosperity and economic growth. The purpose of this study was to determine the analysis of how the influence of GDP, labor, the agricultural sector and Natural Resources on the fiscal capacity of districts/cities in Sumatra. The analytical method used in this research is multiple regression analysis. Tests using statistical tests include t-test, F-test and R-square (coefficient of determination) as well as classical assumption test. Where all these tests use the Eviews 10 program tool with Crossectoin data for 154 districts/cities in Sumatra sourced from the Central Statistics Agency. The results of the analysis show that GRDP, labor, the agricultural sector and Natural Resources have a positive and significant influence on the Fiscal Capacity of Districts/Cities in Sumatra 2019.